Art Therapy: Apa Peran Lansia di Lingkungan Panti Wreda Nazerth ? - Amanda Tiara Kusuma; Novitawati Nur Safitri; Ditami Mega Prilani; Nindhira Trias Pramudita (Universitas Katolik Parahyangan, 2023)
The aim of this observation was to determine the influence of art therapy on the role of elderly individuals in enhancing self-compassion among the elderly at Nazareth Elderly Home. The observation employed a single case design method. Measurement of self-compassion was conducted using a daily self-compassion checklist based on the components of self-compassion developed by Neff. Data were analyzed through visual inspection using graphs that depicted participant changes across phases. The analyzed changes encompassed mean changes, stability, and trends. The analysis was also supported by observational data and interviews. The findings revealed that two out of three participants experienced an increase in average self-confidence during the intervention phase. The remaining participant exhibited slightly lower average self-compassion scores during the intervention phase. Overall, participants responded with diverse yet positive reactions during the intervention phase.